If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3s + -3 = 3 Reorder the terms: -3 + 3s = 3 Solving -3 + 3s = 3 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3s = 3 + 3 Combine like terms: -3 + 3 = 0 0 + 3s = 3 + 3 3s = 3 + 3 Combine like terms: 3 + 3 = 6 3s = 6 Divide each side by '3'. s = 2 Simplifying s = 2
| 2(8-3)=4x-9 | | 10=12-2f | | -3(6-2x)=4(8+4) | | 2y-6+xy-3x= | | -3(6-2x)=4(8+5) | | 4z+10=18 | | ln(2x-99)=0 | | (x-y)x/y=y/x-y(x-y) | | 3.14(5)2(8)= | | X+SqrtX+3=3 | | 8cos(3x)-4*(sqrt(3))=0 | | 17-x/-2=10 | | 17-x/=10 | | ysquared+y=20 | | u/6=-24 | | f(x)=3x^2+7x-9 | | 8x-7y+92=-11 | | 5×4×6/1/2 | | 8ln(x-5)=12 | | 6x+7y-32=-12 | | 2x^3-6x+6=0 | | tan(51)=25/x | | 5x+6y+42=10 | | 10[x]= | | 120x+56y=498 | | .5x-1.5=0 | | 13y-39= | | 2x(3x+4)=6x+8 | | (X)=x(x+7) | | 8x+3=23+4x | | 4ln(x-5)=3 | | x^2+6x+27=22 |